The Challenges of Science Writing (2011)
In this article, Carlos Andrés Buitrago, participant of Expeditions to knowledge and member of the writing workshop on science presents his views on science writing: “I have never considered myself a writer, I am just a fan of putting words together; As such, I love taking on new challenges that constantly show me how much I still have to learn. The most recent of them: the children's university science writing workshop ”.